A study on the financial feasibility of compliant ship recycling yards in Bangladesh - Dipto, Shaumik Sharif; Rahman, Hafizur; Mehtaj, Nafisa; Mawla, Muhammad Sirazul; Zakaria, N M Golam; Dev, Arun Kr (Journal of Naval Architecture and Marine Engineering, 2023)
Ship recycling is one of the most promising industries for Bangladesh. A significant amount of local steel demand is fulfilled by scrap metals from ship recycling yards. Bangladesh has been maintaining a competitive position in the ship recycling sector along with China, India, and Pakistan. But, in the absence of substantial workplace safety and infrastructure development and for not following international regulations, Bangladesh may lose its market share to other countries in this sector. This paper presents a financial analysis to establish compliant ship recycling facilities that will fulfill the Hong Kong Convention (HKC) requirements. This analysis has considered all the facilities of a compliant ship-recycling yard, including impermeable floors, mechanized systems, oily water separators, firefighting systems, and other special features. The worthiness, scalability, and sustainability of investing in the development of compliant ship recycling facilities have been assessed from Bangladesh’s perspective and the benefits over the conventional ones have been discussed. Also, the challenges for ship recyclers and their prevalent perspective toward establishing compliant ship recycling facilities have been depicted. Lastly, recommendations have been suggested to assist the ship recyclers in Bangladesh by encouraging them to invest and enable HKC-compliant ship recycling to harness long-term economic rewards. J. Nav. Arch. Mar. Engg., Vol 20(2), December, 2023; p 1-8